Smart Vision System for Car Tire Condition Monitoring - Daud, Mohd Razali (2006)
Car tire failure is one of the major causes of serious accident. To reduce the accidents, the US National Highway Transport Safety Administration (US NHTSA) has passed a legislation requiring all new passenger cars to be equipped with Tire Pressure Monitoring System (TPMS) starting from November 2006. However, according to automotive experts, tire failure could also originate from excessive tread wear and other several causes.